OPTIMASI ANGLE OF ATTACK UNTUK PENINGKATAN KOEFISIEN LIFT PADA AIRFOIL TURBIN ANGIN SUMBU HORISONTAL - Christian Pangraldi; Fandi Dwiputra Suprianto; Teng Sutrisno (Petra Christian University, 2013)
Wind turbine application as the use of renewable energy sources has been widely used recently as an alternative energy in goal replacing non-renewable energy. This thesis focuses on the optimization of other research conducted lift coefficient of horizontal wind turbine blades. During this optimization systems in wind turbines is still not been developed widely so that the level of efficiency still needs to be researched and developed. This optimization, is expected to improve the efficiency and applicability of horizontal wind turbine especially in energy-efficient buildings that will be built by Petra Christian University.Optimization is done starting from the assessment of AoA on 3 pieces of the NREL type S airfoil, the validation of numerical experiments, and more complex system of blade configurations as the optimization project. Numerical assessments were performed using CFD (Computational Fluid Dynamics) software.From the results of assessments conducted, Angle of Attack the optimal airfoil S-833 (primary) is at AoA 8 ˚, while for S-834 (tip) is 8.5 ˚, and for S-835 (root) is 7 ˚. This study has been able to run well by getting trend graphs are virtually identical, but there are some differences in the validation study numerically the experiment due to limitations in the manufacturing of the experimental device.